Stock market anomalies: The day of the week effects, evidence from Borsa Istanbul - Hülya Cengiz; Ömer Bilen; Ali Hakan Büyüklü; Gülizar Damgacı (Journal of Global Entrepreneurship Research, 2017)
This study was conducted to investigate the market anomalies in the Borsa Istanbul Index (BIST). The scope of this study is to examine the Monday effects in BIST that are stock index of Turkey with an data set that contains daily stock prices between 02.01.2010 and 22.10.2014. The stock returns of the 289 companies were calculated according to the daily historical stock prices of companies. These returns were classified based on the sectors, and statistically analysed if the days of the week had any effects on Monday when the daily stock returns of Monday were fixed constant. The findings showed that the stock returns on Monday were affected by the other days. These effects were mostly negative, and varied according to the stocks and sectors. Thursday and Friday had the highest effect, whereas Tuesday had the least effect on the stocks. The results show that the stock market in Turkey has market anomaly, and BIST is not an efficient market.
Keywords: 650; The day of week effects; Market anomalies; Market efficiency; Monday effects